Overexpression of a key regulator of lipid homeostasis, Scap, promotes respiration in prostate cancer cells. Issue 7 (27th February 2013) - Prabhu, Anika Vinayak; Krycer, James Robert; Brown, Andrew John
Abstract : Prostate metabolism is unique, characterised by cholesterol accumulation and reduced respiration. Are these related? We modulated cholesterol levels and despite changes in mitochondrial cholesterol content, we saw no effects on lactate production or respiration. Instead, these features may be related via sterol regulatory element‐binding protein 2 (SREBP‐2), the master transcriptional regulator of cholesterol synthesis. SREBP‐2 diverts acetyl‐CoA into cholesterol synthesis and may thus reduce respiration. We examined LNCaP cells overexpressing the SREBP‐2 regulator, Scap: although having higher SREBP‐2 activity, these cells displayed higher respiration. This striking observation warrants further investigation. Given that SREBP‐2 and Scap are regulated by factors driving prostate growth, exploring this observation further could shed light on prostate carcinogenesis. Abstract : ► Prostate cells have low respiration and high cholesterol levels. Are they related? ► Changing cholesterol levels altered mitochondrial cholesterol but not respiration. ► Scap drives lipid accumulation; thus Scap overexpression should reduce respiration. ► Remarkably, we found the contrary: overexpression of Scap promotes respiration.